Edge cases in animal research law: Constituting the regulatory borderlands of the UK's Animals (Scientific Procedures) Act. (December 2021) - Palmer, Alexandra; Message, Reuben; Greenhough, Beth
Abstract: This paper explores how the boundaries of the UK's Animals (Scientific Procedures) Act (A(SP)A) are constituted, as illustrative of the rising importance of legal procedures around animal research and how these are continuously being challenged and questioned. Drawing on empirical work in animal research communities, we consider how it is decided whether activities are undertaken for an "experimental or other scientific purpose". We do this by focusing on "edge cases", where debates occur about whether to include an activity within A(SP)A's remit. We demonstrate that the boundaries of animal research regulation in the UK are products of past and present decisions, dependencies, and social relationships. Boundaries are therefore not clear-cut and fixed, but rather flexible and changing borderlands . We particularly highlight the roles of: historical precedent; the management of risk, workload, and cost; institutional and professional identities; and research design in constituting A(SP)A's edges. In doing so, we demonstrate the importance of paying attention to how, in practice, animal law requires a careful balance between adhering to legal paragraphs and allowing for discretion. This in turn has real-world implications for what and how science is done, who does it, and how animals are used in its service. Highlights: UK animal research law covers activities done for "an experimental or other scientific purpose". Whether this criterion is met is debated at "edge cases". Examples: medicine production, wildlife tracking, fisheries and veterinary clinical research. Legal boundaries flexible, shaped by past/present decisions and social relationships. Key factors: precedent, risk/workload/cost management, identity, study design.